SOCIAL REPRESENTATIONS OF BREASTFEEDING AMONG PREGNANT AND POSTPARTUM WOMEN IN PRIMARY HEALTH CARE - Santana, Nayolle Barbosa Emerick; Souza, Yasmin Alves da Luz; Morais, Emanuelly Garcia de Sousa; Soares, Mariana Linhares Pereira; Rodrigues, Luciano Antonio (Seven Editora, 2026)
The gestational period is a time filled with uncertainties, particularly for first-time mothers, leading to frequent doubts regarding breastfeeding due to the many myths that have been passed down through generations. This study aimed to assess the social representations of breastfeeding among pregnant and postpartum women receiving care in Primary Health Care services in the municipalities of Pancas-ES and Colatina-ES, Brazil. This is an observational, descriptive, cross-sectional study with a qualitative approach. The research participants were pregnant women receiving prenatal care at Basic Health Units (BHUs) in the aforementioned municipalities, as well as postpartum women. For data collection, recorded interviews were conducted using a semi-structured questionnaire as a guide. For data analysis, the qualitative information was processed after the recorded interviews were completed, digitized, and transcribed for semantic analysis, with evocations extracted and examined using the software openEVOC 0.92. This tool was used to identify the probable central nucleus and peripheral system of the social representations held by the study participants. The results revealed that the central terms “love,” “fear,” and “health” reflect an ambivalent perception of breastfeeding—viewed as an act of affection and care, yet accompanied by feelings of insecurity and anxiety. The study highlights the need to strengthen educational initiatives within Primary Health Care, emphasizing the role of nurses and the multidisciplinary team in order to enhance follow-up care, provide continuous support, and demystify beliefs that undermine breastfeeding practices.DOI: https://doi.org/10.56238/sevened2026.008-103